P206 Experience of establishing funding for a home IV service for bronchiectasis. (12th November 2015) - Booth, A; McCleary, A; Thomas, RA
Abstract : Background: The benefit of intravenous (IV) antibiotics in bronchiectasis has been established, 1 and IV antibiotics can be safely delivered in a domicillary setting. 2 We report on the experience of obtaining funding through the CCG to establish a service delivering IV antibiotics safely and effectively to people with bronchiectasis at home. Methods: The model for home IV antibiotics involved a vascular surgeon placing a PICC line on day one under guided ultrasound, and an initial review by specialist nurse and physiotherapist. The specialist nurse administered the first dose. Education on line care, anaphylaxis and potential complications was provided. Drugs were delivered via a homecare company, Calea, and home IV doses were administered by specialist nurses from the homecare company. At the end of the course patients were reviewed by the specialist bronchiectasis nurse. Results: Negotiations with the CCG agreed funding for the service with 7.5 h of specialist nurse time and to meet the costs of the homecare company. Between July 2014 and July 2015 9 patients underwent 10 IV courses. A total of 132 days IV antibiotics were given, with 96 (73%) being given at home. This saved bed days, at an estimated saving of £26, 400. Seventy seven home visits were conducted by the homecare company specialist nurses at a cost of £5625 and the homecare drug cost was £6134 (total £11, 759 or £1, 175 per course). Overall cost savings amounted to approximately £20, 266 for the ten courses, or £2, 026 per course. One patient had to return to hospital for replacement of their line due to mechanical phlebitis, but was still able to complete the entire course. Qualitative feedback is being sought via patient questionnaires, and has proved very positive. Conclusion: Administering IV antibiotics at home for people with bronchiectasis is safe, reduces inpatient bed days and is cost effective. References: 1 Murray MP, Turnbull K, Macquarrie S, Hill AT. Assessing response to treatment of exacerbations of bronchiectasis in adults. Eur Respir J . 2009;33 :312–8 2 Bedi P, Sidhu MK, Donaldson LS, et al . A prospective cohort study of the use of domicillary intravenous antibiotics in bronchiectasis. NPJ Prim Care Respir Med . 2014;24 :14090